Incentive Effects of Transfers within the Extended Family: The Case of Indonesia - Dana Schüler (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
This study sheds light on the efficiency of informal mutual insurance systems. Evidence on the behavioral effects of remittances and inter-family transfers is still rare. This paper intends to analyse the incentive effects of inter-family transfers in Indonesia with improved econometric techniques. First differences and three-stage least squares are used to analyse incentive effects on working hours. The endogeneity of transfers received and of the number of migrants sent away are explicitly taken into account. Furthermore, different sectors of employment are distinguished in the analysis. The empirical analysis indicates that inter-family transfers have an adverse influence on work effort in the informal and non-agricultural sector of the economy. Precisely, household members of working age reduce normal hours worked. No evidence is found that child work is reduced. However, the negative incentive effect is partly compensated by migrants, who are recipients rather than providers of transfers in the short run.
Keywords: 330; Remittances; Transfers; Incentives; Three-Stage Least Squares